ADAPTATION OF MSME BUSINESS ACTORS TO SHARIA DIGITAL FINANCE: Case Study On “Cuan Store” Business Actors In Samarinda City (Al Dzahab, 2024)
Purpose: The purpose of this study is to identify how micro, small and medium enterprises "Cuan Store" adapt to using Sharia Digital Finance in their business operations.Design/Methodology/Approach: This research used a descriptive approach along with a qualitative data analysis approach in this study, data collection using interview techniques, observation and literature study.Findings: The results of this study that micro, small and medium enterprises "Cuan Store" have successfully adapted in applying sharia digital finance as a medium in running their business, then the factor of using sharia digital finance in micro, small and medium enterprises is very significant because many "Cuan Store" customers have used sharia digital finance as a payment transaction,  as for the impact on the use of sharia digital finance has a positive influence on micro, small and medium enterprises "Cuan Store".Research Implications: The existence of sharia digital services encourages micro, small and medium enterprises to continue learning about sharia principles. Due to the fact that many customers of "Cuan Store" have used Islamic digital finance as a way of payment, the factor of using Islamic digital finance on micro, small and medium enterprises is very significant. In addition, the effect of using Islamic digital finance has a positive impact on the micro, small and medium enterprises of "Cuan Store", because the existence of Islamic digital services encourages micro, small and medium enterprises to continue learning about sharia principles.